Studi tentang Ergonomi dan Karakter Psikososial bagi Yatim Piatu di LKSA Yayasan Kyai Raden Mohammad Kasiman Kota Blitar - Shofwan, Arif Muzayin Shofwan (Ta'lim : Jurnal Multidisiplin Ilmu, 2024)
The Kyai Raden Mohammad Kasiman Child Social Welfare Institution (LKSA) Blitar City is an institution initiated by H. Masjhun Sofwan, S.H and aims to provide welfare for orphans and orphans. This case study research using data triangulation will examine ergonomic issues and psychosocial characteristics for orphaned children at the Kyai Raden Mohammad Kasiman Child Welfare Institution (LKSA) Blitar City. This research found several things as follows. First, the problems that need to be improved in ergonomics at the Kyai Raden Mohammad Kasiman Child Welfare Institution (LKSA) in Blitar City include: providing small tables for studying for orphans, providing proper name boards so they are pleasing to the eye, providing flower gardens, cool conditions in the institutional environment, providing adequate learning media for orphans during the teaching and learning process such as laptops, LCDs, and others. Second, several things that need to be considered and developed regarding the psychosocial character of orphans at the Kyai Raden Mohammad Kasiman Child Welfare Institution (LKSA) in Blitar City, include: developing focused attention on orphans from the surrounding environment, developing a focus on learning for orphans, overcoming the problem of easily crying when remembering parents who have died for orphans, motivating enthusiasm for orphans who often feel alone, have economic difficulties, feel inferior, and tend to stay away from the social environment.